PERANCANGAN SISTEM INFORMASI KANTOR DESA BERBASIS WEBSITE SEBAGAI MEDIA PELAYANAN DAN PENGOLAHAN SISTEM KEPEGAWAIAN (Studi Kasus : Desa Sukamanah Kecamatan Baros Kabupaten Serang) - Nabila Putrikinanty (2021)
At this time the condition of the Sukamanah Village Office in providing information services and letter submissions made by the community, personnel data processing systems, and data processing related to information and letter submissions are still both done manually. The results of the current information system at the Sukamanah Village Office, which is still being processed manually, certainly have an impact on the level of community satisfaction and employees who want a faster settlement process on the system. The purpose of this research is to make an information system design at the Village Office based on a website that contains information related to the Village Office, mailing services that can be done by the public online, and a staffing system that can function as personnel data processing and data processing. relating to information and letter submissions submitted by the public. The research method uses Waterfall which consists of 5 stages, namely Requirement, Design, Implementation, Testing, and operation and testing using Black Box Testing. This website-based Village Office Information System is expected to be able to streamline the activities of village employees in carrying out processes in the staffing system and services related to the community. In addition, it can make it easier for the community to access information related to the Sukamanah Village office and submit letters that only need to be done from home without having to come directly to the Sukamanah Village office.